Non-Invasive Diagnosis and Monitoring of Diabetic Nephropathy: Assessment of Renal Function and Fibrosis by Diffusion Kurtosis Imaging - Yuan JL; Hu LA; Wang XY; Shi ZY; Chen T; Huang XZ; Wu Y; Cai QJ; Yang ZX; Chen XY; Yuan L; Zhang Y (International Journal of General Medicine)
Jian-Lei Yuan,1,2,* Li-Ao Hu,1,2,* Xin-Yu Wang,2,3,* Zhao-Yu Shi,1,2 Ting Chen,1,2 Xin-Zhong Huang,1,2 Yu Wu,1,2 Qiu-Jie Cai,1,2 Zi-Xu Yang,1,2 Xin-Yi Chen,4 Li Yuan,1,2 Yuan Zhang1,2 1Department of Nephrology, Affiliated Hospital of Nantong University, Nantong, 226001, People’s Republic of China; 2Medical School of Nantong University, Nantong, 226001, People’s Republic of China; 3Department of Medical Imaging, Affiliated Hospital of Nantong University, Nantong, 226001, People’s Republic of China; 4Nanjing Medical University School of Basic Medical Sciences, Nanjing, 211166, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuan Zhang, Email zhangy.nt.nd@ntu.edu.cn Li Yuan, Email yuanlint@163.comBackground: This monocentric, cross-sectional study explored the use of diffusion kurtosis imaging (DKI) as a non-invasive means to diagnose and monitor diabetic nephropathy (DN).Methods: Patients with diabetes mellitus (DM, n = 11), mild DN (N = 14), and severe DN (n = 29) were recruited. Eight DKI metrics (MK, MD, Da, Dr, Ka, Kr, FA, FAk) were determined from the imaging results, and their correlations with routine laboratory results were analyzed. The receiver operating characteristic (ROC) curves were plotted, and the diagnostic value of the DKI metrics was analyzed. In addition, renal biopsy was carried out for ten DN patients who had appropriate indications. Their interstitial fibrosis and tubular atrophy (IFTA) score and the fibrosis ratio of cortical area (F%) were analyzed in combination with the DKI metrics.Results: The progression of DN, reflected by the estimated glomerular filtration rate (eGFR), was accompanied by rising mean kurtosis (MK) and axial kurtosis (Ka) along with decreasing mean diffusivity (MD), axial diffusivity (Da), and radial diffusivity (Dr). Whereas MK was correlated negatively with hemoglobin (Hb) and eGFR and positively with neutrophil gelatinase-associated lipocalin (NGAL), cystatin C (CysC), and serum creatinine (Scr), MD, Da, and Dr were positively correlated with Hb and eGFR and negatively correlated with CysC and Scr. For the biopsied patients, MK was positively correlated with IFTA, and fractional anisotropy of kurtosis (FAk) was negatively correlated with F% and IFTA. Among the DKI indicators, MK had the highest AUC (0.922, 95% CI: 0.843– 1.000).Conclusion: The noninvasive monitoring of DN was feasible with DKI, and MK could indicate the renal function and fibrosis of DN patients. Changes in MK may also serve as a biomarker to assess treatment response (eg, microstructural improvement) after therapeutic interventions (eg, drug therapy for diabetic nephropathy, anti-fibrotic therapy).Plain Language Summary: Diabetic nephropathy (DN) is a serious kidney complication of diabetes and the leading cause of end-stage renal disease. While imaging tools like ultrasound, CT, and standard MRI are widely used to evaluate kidney structure and blood flow, they play a limited role in diagnosing or monitoring DN. There is a growing need for non-invasive methods that can detect early changes and track disease progression more precisely. Diffusional Kurtosis Imaging (DKI) is an advanced MRI technique that captures the complexity of water movement in tissues, offering insights into kidney microstructure. The present study analyzed, in DN patients, eight DKI metrics—mean kurtosis and diffusivity (MK and MD), axial and radial diffusivity and kurtosis (Da, Dr, Ka, Kr,), fractional anisotropy (FA), and fractional anisotropy in kurtosis (FAk)—and compared them to standard lab markers and biopsy results. Among all DKI measures, MK showed the strongest correlation with kidney function and fibrosis. Specifically, higher MK values were associated with worse kidney function (lower hemoglobin and eGFR, higher creatinine, NGAL, and cystatin C) and more severe tissue damage (higher fibrosis scores on biopsy). MK also achieved the highest diagnostic accuracy (AUC = 0.922) in distinguishing disease severity. These findings suggest that DKI, and MK in particular, can serve as a powerful, non-invasive biomarker for assessing kidney damage and fibrosis in DN patients. MK may also help track treatment response, offering a way to monitor improvements in kidney microstructure following therapies.Keywords: diabetes mellitus, diabetic nephropathy, diffusion kurtosis imaging, magnetic resonance imaging, mean kurtosis